2020
DOI: 10.1111/tmi.13481
|View full text |Cite
|
Sign up to set email alerts
|

Health interventions among mobile pastoralists: a systematic review to guide health service design

Abstract: Objective Mobile pastoralists are one of the last populations to be reached by health services and are frequently missed by health campaigns. Since health interventions among pastoralists have been staged across a range of disciplines but have not yet been systematically characterised, we set out to fill this gap. Methods We conducted a systematic search in PubMed/MEDLINE, Scopus, Embase, CINAL, Web of Science, WHO Catalog, AGRICOLA, CABI, ScIELO, Google Scholar and grey literature repositories to identify rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 108 publications
(108 reference statements)
1
10
0
1
Order By: Relevance
“…Health system leaders, in response to the emergency, successfully implemented a combined community level and fixed health service delivery points to reach the pastoralist community. This finding aligns with previous research highlighting the importance of flexible service delivery models such as mixed mobile and temporary fixed options, that cater to the sociocultural context and ensure service acceptability within pastoralist communities 24. Moreover, a study from Ethiopia found that mobile health team played a vital role in delivering health and nutrition services to mobile community 25.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Health system leaders, in response to the emergency, successfully implemented a combined community level and fixed health service delivery points to reach the pastoralist community. This finding aligns with previous research highlighting the importance of flexible service delivery models such as mixed mobile and temporary fixed options, that cater to the sociocultural context and ensure service acceptability within pastoralist communities 24. Moreover, a study from Ethiopia found that mobile health team played a vital role in delivering health and nutrition services to mobile community 25.…”
Section: Discussionsupporting
confidence: 89%
“…This finding aligns with previous research highlighting the importance of flexible service delivery models such as mixed mobile and temporary fixed options, that cater to the sociocultural context and ensure service acceptability within pastoralist communities. 24 Moreover, a study from Ethiopia found that mobile health team played a vital role in delivering health and nutrition services to mobile community. 25 These findings consistent with this study, where the combined approach of community-based outreach and fixed health service delivery points effectively extended health service during drought and food insecurity emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Migration changes the distance to markets and services, already suboptimal in origin villages. A 2005 survey of nomadic Fulani found that 99 percent of children had not received routine childhood immunisations due to their mobility and remote locations (Wild et al, 2020).…”
Section: Pathways To Diseasementioning
confidence: 99%
“…Dalam situasi pandemi seperti ini, banyak pihak telah melakukan berbagai upaya komunikasi secara serentak dan dalam waktu yang sama. Di satu sisi situasi seperti ini memberikan keuntungan bagi publik untuk secara cepat mendapatkan informasi terkini (Wild et al, 2020). Namun di sisi lain mempunyai kelemahan yaitu pesan yang terlalu banyak dikeluarkan, bersifat random (impulsive) dan selalu berubah akan menciptakan noise yang mengganggu penerimaan pesan dan pada akhirnya menghalangi orang untuk memahaminya dan mengubah perilakunya (Ahorsu et al, 2020).…”
Section: Metodeunclassified